ASBAB AL-NUZUL SURAH MU’AWIDZATAIN AND ITS INTERPRETATION IN SCHLEIERMACHER’S HERMENEUTICS REVIEW - Arif Makmun Rifa'i (Institut Agama Islam Ngawi, 2014)
Common problem related with text is how to understand the text as something that comes from the past in the present world. Qur'an from the past also has similarity. The same problem when faced with the Qur'an is how to understand the Qur'an from the past that are relevant to the modern world. To make the Qur'an in order to be relevant in the modern world, twe study of the method should not be stopped but the method needs to be updated and reviewed continuously. In an effort to update this method, thus Schleiermacher’s hermeneutics method presented here. In reviewing asbab al-nuzul using Schleiermacher's hermeneutics, the method used is descriptive method where in addition to explained, describe or explain, also performed a critical analysis, meant conducting certain considerations on the interpretation theory of Schleiermacher with asbab al-nuzul to the interpretation surah Mu'awizatain alignment thus found and got distortion, although, at a certain level is not touch by Schleiermacher, but we can use approaches to his theory.